Analisis Faktor-Faktor yang memengaruhi Literasi Keuangan Syariah Karyawan Lembaga Keuangan Syariah: - Yudi Saeful Rizal,; Qurroh Ayuniyyah; Hendri Tanjung (LPPM Institut Nasional Laa Roiba Bogor, 2023)
According to the results of a literacy survey conducted by the OJK, the level of literacy and public understanding of Islamic financial products and services is still low, even though in order to properly implement sharia principles, practitioners of Islamic financial institutions (LKS) need to have good Islamic financial literacy, especially employees of institutions. Islamic finance because apart from being a service provider, it also plays a role in educating customers in understanding the products offered. This is the background of the author to analyze how the level of Islamic financial literacy of employees of Islamic financial institutions and the factors that influence it. This research was conducted at KSPPS Baytul Ikhtiar. The population in this study was 367 with a sample of 232 respondents. Data collection techniques were taken by survey method through two instruments, namely questionnaires and interviews. The data analysis carried out was descriptive analysis, data quality test, classical assumption test and multiple linear regression analysis. The results of this study indicate that the level of Islamic financial literacy of KSPPS Baytul Ikhtiar employees is in the medium category, the financing aspect is in the high category, and the basics of Islamic finance is in the medium category. in the aspect of savings, insurance and sharia investment into the low category. From the results of Multiple Linear analysis, the variables of religiosity and gender have no effect on Islamic financial literacy. Variables of work experience, education level and Islamic Financial Training have a significant effect on Islamic financial literacy. Then the results of the simultaneous test (F) show that the variables of religiosity, gender, work experience and education level together have a significant effect on Islamic Financial Literacy for Baytul Ikhtiar KSPPS employees. Keywords: Islamic Financial Literacy; Islamic Financial Institutions; Sharia Financial Inclusion